2000
DOI: 10.2519/jospt.2000.30.8.444
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Tibial Stress Fractures Using Therapeutic Continuous Ultrasound

Abstract: Study Design: One-group discriminant analysis. Objective: To determine whether 1 MHz of continuous ultrasound can identify tibial stress fractures in subjects. Background: Stress fractures can lead to loss of function or to more serious nonunion fractures. Early diagnosis is important to reduce the risk of further injury and to assure a safe return to activity. Therapeutic ultrasound has been reported to be an accessible, less expensive alternative in diagnosing stress fractures compared with other diagnostic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 18 publications
(1 reference statement)
0
38
0
1
Order By: Relevance
“…Only studies utilizing the ultrasound and tuning fork tests have reported sensitivity and specificity values ( Table 2). Authors that used ultrasound 5,10,28,34,38,43 used a variety of frequencies and intensities, and many of the studies did not document specific parameters utilized in their assessment of tibial stress fractures. Utility of the fulcrum test has only been reported in association with femoral shaft stress fractures.…”
Section: Discussionmentioning
confidence: 99%
“…Only studies utilizing the ultrasound and tuning fork tests have reported sensitivity and specificity values ( Table 2). Authors that used ultrasound 5,10,28,34,38,43 used a variety of frequencies and intensities, and many of the studies did not document specific parameters utilized in their assessment of tibial stress fractures. Utility of the fulcrum test has only been reported in association with femoral shaft stress fractures.…”
Section: Discussionmentioning
confidence: 99%
“…36,51 Scintigraphy is able to diagnose stress fractures by identifying areas of increased uptake of the radioisotope 3 and has a reported sensitivity of 100% and specificity of 76%. 8,41 MRI has been shown to have comparable sensitivity 3,41 and superior specificity to scintigraphy for assessment of bone pathology.…”
Section: T T Conclusionmentioning
confidence: 99%
“…This void is apparent when tracing references from several textbooks and published articles, which provide no data to support the suggested transducer velocity. [1][2][3][4][5]8,9,10,12,[16][17][18][20][21][22]24,[26][27][28] High beam nonuniformity ratio (BNR) is typically cited as a reason to move the transducer head in this fashion to decrease the risk of causing pain to the patient, while maximizing thermal effects. [6][7][8]23,29 Today, manufacturers are producing transducers that contain crystals with lower BNRs, which may allow for transducers to be moved at slower rates, while still protecting the patient.…”
mentioning
confidence: 99%